Japanese Landscape in Polish Travel Writing in 1880s and 1890s - Gromadzka, Oliwia (Porównania, 2021)
The article aims to analyze the portrait of the Japanese landscape that emerges from Polish travel writing published in late 19th century. Three (and thus all known) texts written by Polish travelers Karol Lanckoroński, Paweł Sapieha and Hugo Zapałowicz are analyzed. The authors traveled independently to Japan at the end of 1880s. The reflection focuses on the individual features of the narrative, such as comparisons, landscape representations, intercultural relations or stereotypes about non-European societies, which constitute a distinctive description of Japan characterized by a colonial view.